The Effect of Transformational Leadership Style and Compensation on Employee Performance at Pamella Supermarket Employees 7 - Yuyun Fitri Astuti (Indonesia Accounting Research Journal, 2021)
This research is a  replication research from Rolasmana's research (2013). This research includes causal associative research using a quantitative approach. This population is a population study because the number of subjects is less than 100 people, so that all members of the population are taken. The population of this study were all Pamella Supermarket 7 employees, totaling 65 people. Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple regression. The results of the research at the 5% significance level show that: (1) Transformational leadership style has a positive effect on employee performance. This is evidenced by the beta coefficient (β) 0.317 (**p<0.05; p=0.000) and the contribution of the influence of transformational leadership style on employee performance is (∆R2) 0.088; (2) Compensation has a positive effect on employee performance. This is evidenced by the results of the beta coefficient (β) 0.236 (**p<0.05; p=0.008) and the contribution of the effect of compensation on employee performance (∆R2) 0.039; and (3) transformational leadership style and compensation have a positive influence on employee performance. This is evidenced for transformational leadership style with a beta coefficient (β) of 0.286 (**p<0.05; p=0.000) and for compensation with a beta coefficient (β) of 0.174 (*p<0.05; p=0.031). The contribution of transformational leadership style and compensation to employee performance is (∆R2) 0.108.